1998
DOI: 10.1152/jappl.1998.85.5.1762
|View full text |Cite
|
Sign up to set email alerts
|

Increased compliance in diaphragm muscle of the cardiomyopathic Syrian hamster

Abstract: We investigated the hypothesis that diaphragm compliance was abnormal in cardiomyopathic Syrian hamsters (CSH), an experimental model of myopathy. The passive elastic properties of isolated diaphragm muscles were analyzed at both the muscle and sarcomere levels. We used the following passive exponential relationship between stress (sigma) and strain (epsilon): sigma = (Eo/beta) (ebetaepsilon - 1), where Eo is the initial elastic modulus and beta is the stiffness constant. Immunocytochemistry procedures were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 35 publications
1
17
0
1
Order By: Relevance
“…The current results are in line with a previous study that reported decreased stiffness of diaphragm bundles from cardiomyopathic hamsters [24]. However, that study was unable to indicate a specific cause for reduced stiffness, because passive tension development of muscle bundles depends on elasticity of both intracellular and extracellular components, e.g.…”
Section: Discussionsupporting
confidence: 90%
“…The current results are in line with a previous study that reported decreased stiffness of diaphragm bundles from cardiomyopathic hamsters [24]. However, that study was unable to indicate a specific cause for reduced stiffness, because passive tension development of muscle bundles depends on elasticity of both intracellular and extracellular components, e.g.…”
Section: Discussionsupporting
confidence: 90%
“…The Young's modulus of the human heart ranges between 200 and 500 kPa in the contracted state (25)(26)(27). Moreover, the left ventricle (LV) has unique mechanical anisotropy, with a measured anisotropy ratio of 2.1, that is essential for proper function (7).…”
Section: Resultsmentioning
confidence: 99%
“…The terrestrial mammalian diaphragm is composed of muscle, a collagenous central tendon and an elastin-rich ligament (Griffiths et al, 1992), each with different mechanical properties. Diaphragm muscle moduli range from 0.2 to 0.8MPa (Coirault et al, 1998;Gates et al, 1980), and a value of 33MPa has been used to model the tendon (Behr et al, 2006). The central tendon may be reduced or absent in cetaceans (Dearolf, 2002), but diaphragm movement may be constrained by other structures, including surface tendons that may be comparable to the elastic ligament and dorsolateral connective tissue connections to the subdermal sheath (Dearolf, 2002).…”
Section: Diaphragm Deformationmentioning
confidence: 99%